2021
DOI: 10.1088/1361-6560/ac0e77
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment classification using combined structural and diffusion imaging biomarkers

Abstract: Alzheimer's disease is a multifactorial neurodegenerative disorder preceded by a prodromal stage called mild cognitive impairment (MCI). Early diagnosis of MCI is crucial for delaying the progression and optimizing the treatment. In this study we propose a random forest (RF) classifier to distinguish between MCI and healthy control subjects (HC), identifying the most relevant features computed from structural T1-weighted and diffusion-weighted magnetic resonance images (sMRI and DWI), combined with neuro-psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 45 publications
0
9
0
4
Order By: Relevance
“…The MDI indicates the degree of impurity (classification capability) for each variable according to the GINI index, which measures the probability of a particular variable being wrongly classified when it is randomly chosen. This algorithm has been selected because of its ability to assign the importance of biological features [ 11 , 23 , 24 ]. Furthermore, in a previous work in which various feature selection algorithms were compared, the MDI-based approach was one of the best performing [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The MDI indicates the degree of impurity (classification capability) for each variable according to the GINI index, which measures the probability of a particular variable being wrongly classified when it is randomly chosen. This algorithm has been selected because of its ability to assign the importance of biological features [ 11 , 23 , 24 ]. Furthermore, in a previous work in which various feature selection algorithms were compared, the MDI-based approach was one of the best performing [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many different methods and algorithms were introduced to identify the AD micro macrostructural changes such as machine learning (ML) [8] and deep learning especially convolutional neural network (CNN). They capture low-to-high-level features from an input dataset without human intervention.…”
Section: Related Workmentioning
confidence: 99%
“…6 Furthermore, multiple studies have found that the putamen, thalamus, and other structures are all affected by AD. 7,8 On the other hand, diffusion tensor imaging (DTI) is a new MRI modality introduced to detect microstructural changes that are undetectable in anatomical scans. 9 Hence, it provides additional information to the sMRI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations